The Textile-Clothing Value Chain in India and Bangladesh : How Appropriate Policies Can Promote (or Inhibit) Trade and Investment - Kabir, Mahfuz (World Bank, Washington, DC, 2019)
There are significant value chain linkages between India and Bangladesh, particularly in the textile and apparel sector. India specializes in the upstream segment, supplying such intermediate inputs as silk, cotton, yarn, and fabrics to Bangladesh. Bangladesh specializes in the downstream final apparel segment, exporting worldwide as well as to India. Tariffs and nontariff barriers in both countries inhibit the growth of value chain linkages. In addition, subsidies and other industrial policies in India distort incentives away from the natural pattern of specialization. The results of a new survey of textile and clothing firms in both countries corroborate these findings. Reforms in trade policy (including rules of origin), trade facilitation, trade-related standards, and institutions could help both countries better take advantage of value chain linkages.